Advance in Drug Delivery for Ageing Skeletal Muscle - Li, Yi; Chen, Ming; Zhao, Yanpeng; Li, Ming; Qin, Yong; Cheng, Shi; Yang, Yanyu; Yin, Pengbin; Zhang, Licheng; Tang, Peifu (Frontiers in Pharmacology, 2020)
The age-related loss of skeletal muscle, sarcopenia, is characterized by progressive loss of muscle mass, reduction in muscle strength, and dysfunction of physical performance. It has become a global health problem leading to several adverse outcomes in the ageing population. Research on skeletal muscle loss prevention and treatment is developing quickly. However, the current clinical approaches to sarcopenia are limited. Recently, novel drug delivery systems offer new possibilities for treating aged muscle loss. Herein, we briefly recapitulate the potential therapeutic targets of aged skeletal muscle and provide a concise advance in the drug delivery systems, mainly focus on the use of nano-carriers. Furthermore, we elaborately discuss the prospect of aged skeletal muscle treatment by nanotechnology approaches.